Interrupted Social Peace: Hate Speech in Turkish Media - H. Esra Arcan (IAFOR Journal of Media, Communication & Film, 2013)
Hate speech can play a key role in interrupting social peace. Recent studies have shown that the number of headlines and news stories that vilify specific groups on the basis of ethnicity, religion, gender or sexual orientation have increased in Turkish media. Since media narratives and news reports affect the construction and representation of social groups, this study attempts to uncover hate speech strategies that specifically target ethnic and religious minority groups in Turkey. Reviewing hate speech in mainstream Turkish media, the article poses two important questions: (1) How, and to what extent, is hate speech employed? (2) What types of discourse strategies are constructed in the news? Answering these questions, the article will then discuss related issues and use critical discourse analysis methodology. Also, the relationship between hate crimes and hate speech will be investigated, revealing the primordial importance of combating hate speech.